Ligated Transition Metal Clusters in Solid-state Chemistry The legacy of Marcel Sergent - Halet, Jean-François.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume dedicated to the memory of Marcel Sergent who was a leader in this field for many years, addresses past achievements and recent developments in this vibrant area of research. Large classes of ligated transition metal clusters are produced either exclusively or most reliably by means of high-temperature solid-state reactions. Among them, the Chevrel-Sergent phases and related materials have generated enormous interest since their discovery in 1971. Today, these materials and their numerous derivatives still constitute a vivid area of research finding some applications not only in superconductivity, but also in catalysis, optics or thermoelectricity to mention a few. .
Chapter 1. Chevrel-Phases: Genesis and Developments -- Chapter 2. Octahedral chalcogenide rhenium clusters: From solids to isolated cluster complexes -- Chapter 3.Exploring the Breadth of Terminal Ligands Coordinated in [Mo6X8]4+ and [Re6Q8]2+ Based Cluster Complexes -- Chapter 4. Rhenium Hexanuclear clusters: Bonding, spectroscopy and Applications of Molecular Chevrel Phases -- Chapter 5 -- Thermoelectric Properties of Ternary and Quaternary Mo6 and Mo9 Cluster Selenides -- Chapter 6. Inorganic Niobium and Tantalum Octahedral Cluster Halide Compounds with Three-dimensional Frameworks: A Review on their Crystallographic and Electronic Structures.
Keywords: Organometallic chemistry .; Inorganic chemistry; Physical chemistry; Spectrum analysis; Catalysis; Organometallic Chemistry; Inorganic Chemistry; Physical Chemistry; Spectroscopy; Catalysis